Civil society versus captured state: a winning strategy for sustainable change. Issue 5 (3rd July 2016) - Lutsevych, Orysia
ABSTRACT: In the West, Ukraine is known as country of wasted potential, and most recently the scene of a proxy war between the West and Russia. What is often missing in the analysis is that, internally, the country faces serious nation- and state-building challenges. These call for development of institutions, values, and behaviours that could sustain an open democratic system of governance. A strong and sustainable civil society is an integral part of such a system. In 2013 a popular uprising toppled the corrupt regime of Victor Yanukovych. This triggered the Russian annexation of Crimea and unleashed a violent separatist movement in Ukraine's industrial heartland, the Donbass. Since 2014 Ukraine has been both under external attack and simultaneously trying to reform its corrupt and captured political system.